Counselor Function in Secondary Schools Highline School District 401; 1969-70 - Maser, Arthur L.; Highline Public Schools, Seattle, WA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The impetus for the study was provided by the widespread disagreement on the counselor's role and function as stated by counselors and administrators. Purposes included: (1) the provision of information about the counselor's role and function; (2) the resolution of confusion concerning the counselor's role; and (3) the improvement of communication among building staffs about counselors' roles and functions. The Counselor Function Inventory (CFI), which consists of 77 statements of function in seven areas of counselor services, was selected as the instrumentation. All full-time junior and senior high school counselors and administrators, as well as teachers from two of the district's schools, provided the sample. Data collection procedures were explained and data analysis presented. Results showed insignificant differences in perception of the counselor's function. A staff study of the results was summarized. (TL)
Availability: Dr. Arthur L. Maser, Research Department, Highline Public Schools, P.O. Box 66100, Seattle, Washington 98166 (No price is quoted.).
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Counselors; Guidance Personnel; Guidance; Pupil Personnel Workers; Secondary Schools; Guidance Objectives; Guidance Programs; School Counselors; Secondary Education